Characterization Of Allergens From Dust Mite (Tyrophagus Putrescentiae) - Sew, Yun Shin (2003)
Hypersensitivity to dust mite allergens is one of the most common allergic reactions in the world with estimated 10% of the general population and 90% of individuals suffering from allergic asthma are sensitive to dust mites. Tyrophagus putrescentiae (TP) represents one of the common storage mites which has a worldwide distribution with particularly highly prevalence in tropical and subtropical regions and its explicit allergenic importance in causing mite sensitization has been well documented. In an attempt to evaluate the allergenicity of T. putrescentiae, few immunological tests have been performed on T. putrescentiae crude extracts by using sera from allergic subjects. Dot blot screening revealed that 49.7% of 141 patient sera showed the presence of specific IgE towards TP mite components. There were at least 15 IgE binding components present in TP with molecular weights ranging from 10 to 150 kD with 15 and 77 kD appearing to be major allergens observed after immunoblotting. At the same time, the cross-reactivity studies were carried out in an effort to establish the antigenic relationship between T. putrescentiae and eight other mite species which is important for accurate allergy diagnosis as well as effective immunotherapy for allergic patients. Although most of the mites' allergens share some degree of allergenic cross-reactivity or epitopes with T putrescentiae, those mites somehow also contain unique allergens or epitopes with relatively low crossreactivity with T putrescentiae allergens. Also, cross-reactivity between T putrescentiae and other mite allergens in this study was likely to be the result from multiple sensitizations of allergic subjects to coexisting mite species particularly the principal mite species (Blomia and Dermatophagoides spp. ) in the studied environment.